An efficient and robust continuous-flow bioreactor for the enzymatic preparation of phytosterol esters based on hollow lipase microarray. (15th March 2022) - Xu, Liujia; Wang, Jing; Huang, Fenghong; Zheng, Mingming
Highlights: A novel method for the continuous enzymatic synthesis of PEs was developed. The lipase microarrays based on HMSS showed high activity and stability. The highest productivity for PEs was obtained after 30 days of non-stop operation. Continuous flow modes can remove the by-product and scale up easily compared with batch reactions. Abstract: In this study, a continuous-flow bioreactor packed with well-organized lipase microarrays was developed for the sustainable synthesis of functional lipid-phytosterol esters (PEs). Hollow mesoporous silicon spheres with a suitable pore size were prepared for lipase immobilization, and the hydrophobic modification endowed the lipase with excellent catalytic activity and stability. The results showed that the condensely packed lipase microarrays offered large specific surface areas and guaranteed the thorough interaction between the lipase and substrates in the continuous-flow bioreactor. Meanwhile, the substrate could pass through the reactor at 1 mL/min with a high conversion of 93.6% due to the hollow structure of the packing spheres. Moreover, the reactors were able to produce 1564 g PEs/g catalyst in a continuous 30-day processing period, which set the highest records for PEs synthesis. This sustainable and highly-converting flow system provided a feasible path for scale-up production of PEs in the food processing area.